GAZALİ'YE GÖRE ÖNCÜLLERİN YAPISI - İbrahim Çapak (Felsefe Dünyası)
The issue of premises is rather important for classical logic. For, in a syllogism, if premises are true, the conclusion must be true. Therefore, the truth of premises is crucial. This essay provides al-Ghazali's account of the definition, strtucture and different types of premises.